2015
DOI: 10.1103/physrevb.92.075305
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative soliton protocols in semiconductor microcavities at finite temperatures

Abstract: We consider exciton polaritons in a semiconductor microcavity with a saturable absorber in the growth direction of the heterostructure. This feature promotes additional nonlinear losses of the system with the emergence of bistability of the condensate particles number on the nonresonant (electrical or optical) excitation intensity. Further we demonstrate a new type of bright spatial dissipative exciton-polariton soliton which emerges in the equilibrium between the regions with different particle density. We de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…They have been predicted in several contexts [15,[36][37][38][39][40][41][42] and observed so far mostly in planar cavities [22,43,44]. In addition state-of-the-art investigations describe driven dissipative bright solitons under non-resonant excitation [45,46] for the repulsive BE condensate. In this work we provide an analytical mean field non-equilibrium theory for bright solitons and predict numerically the bright soliton patterns that emerge within an effectively attractive spinor condensate.…”
Section: Introductionmentioning
confidence: 91%
“…They have been predicted in several contexts [15,[36][37][38][39][40][41][42] and observed so far mostly in planar cavities [22,43,44]. In addition state-of-the-art investigations describe driven dissipative bright solitons under non-resonant excitation [45,46] for the repulsive BE condensate. In this work we provide an analytical mean field non-equilibrium theory for bright solitons and predict numerically the bright soliton patterns that emerge within an effectively attractive spinor condensate.…”
Section: Introductionmentioning
confidence: 91%
“…Suitable alternatives have been demonstrated for incoherently pumped polaritons using applied external electric fields, which can cause bistability due to density-dependent lifetimes of electron-hole tunneling [10,11], or through Pockelsinduced birefringence [12]. Theoretical schemes have been proposed to induce polariton bistability through modulational instability [13], through strongly saturated absorption [14], or between condensate wave functions of different parity [15].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting coherent state of polaritons is well described by a nonlinear Schrödinger equation (also known as a Gross-Pitaevskii equation), modified to account for gain and loss in the system [30]. Theoretical studies revealed that this equation supports a variety of spatially nontrivial structures, including: vortices and vortex lattices [31,32]; solitons [33][34][35][36][37]; and various other patterns [38][39][40].…”
Section: Spatial Dynamics Of Polariton Lasing Structuresmentioning
confidence: 99%